Role of cholinergic agents in proliferation and caspase activity of hemin-induced erythroid differentiated K562 cells - AYDIN OMAY, BANU; CABADAK, HÜLYA (TAYLOR & FRANCIS LTD, 2020)
Background: Muscarinic receptors have many functions in the cells and tissues. Acetylcholine (ACh) plays an important role in cellular physiology. ACh also acts at the different parts of the central nervous system and nonneuronal cells. Cholinergic receptors also have different functions in many cell types and tissues. Caspases (cysteine aspartic proteases and cysteine aspartases) are cysteine dependent aspartate-specific proteases. They are an important role in necrosis and cell death and inflammation signaling pathways. They are also the primary mediators of apoptosis. During apoptosis, different caspase types participate in different functions. We have previously shown that carbachol (CCh) inhibits K562 cell proliferation. This study was performed to investigate the anti-tumor efficacy of cholinergic drugs in hemin-induced erythroid differentiated K562 cells. The aim of this study was to address the mechanism of cholinergic drugs on hemin-induced erythroid differentiated K562 cell proliferation and caspase activities. We detected M-3 muscarinic receptor expression in erythroid differentiated K562 cell line. Methods: K562 cells were differentiated with hemin (50 mu M). The expression of the M-3 muscarinic receptor was detected by the western blotting technique. Erythroid differentiated K562 cells treated with CCh (100 mu M). After 24 and 48 h, cells were counted by BrdU cell proliferation kit. Caspase 3,8, and 9 activities were measured by enzyme-linked immunosorbent assay (ELISA) kits according to the manufacturer's instructions. Results: Erythroid differentiated K562 cell proliferation was not significantly increased after CCh treatment. In the meantime, caspases 8 and 9 activities in erythroid differentiated K562 cell line was significantly higher than undifferentiated K562 cells (p < .05).
Keywords: Carbachol; differentiation; caspases; muscarinic receptor; leukemia; apoptosis; NONNEURONAL ACETYLCHOLINE; BIOLOGICAL-SYSTEMS; EXPRESSION; RECEPTORS; MECHANISMS; MOLECULE